Clinical practice patterns in the management of thyroid nodules: The first survey from the Middle East and Africa - Beshyah, Salem; Khalil, Aly (Journal of Diabetes and Endocrine Practice, 2021)
Objective: We sought to scope the practices in managing thyroid nodules in the Middle East and Africa (MEA). Materials and Methods: Survey of a convenience sample of physicians concerned with the management of thyroid disease. Results: Two hundred and twelve responses are included. Fine needle aspiration (FNA) is performed chiefly using ultrasound guidance (74.9%), generally by radiologists (47.1%). Respondents have a lower threshold for FNA than recommended. Management depends on the FNA cytology, with the follicular lesion of undetermined significance/atypia of undetermined significance resulting in repeat FNA for cytology (40.7%), immediate referral for thyroid surgery (32.9%), or molecular testing (13.2%). Follicular neoplasms are referred for lobectomy or total thyroidectomy by 81.6% of respondents. Nodules suspicious for malignancy are referred for thyroid surgery by 76.6% and for molecular testing by 20.1%. Respondents are less likely to perform FNA in an octogenarian than a younger patient with a comparable nodule. For a multinodular goiter, 29.9%, 25.9%, or 17.8% of respondents would, respectively, sample the largest 2–3 nodules, single largest nodule, or all nodules >1 cm in size. During pregnancy, respondents would perform FNA with nodular growth (27.1%) in the absence of nodular growth (25.6%), but more respondents (35.2%) would defer FNA until after pregnancy. Conclusions: The physicians' survey revealed a practice pattern in managing thyroid nodules in the MEA region, including both agreements and deviations from current guidelines. Focused quality assurance exercises, education, and research are needed.
Keywords: Fine needle aspiration; guidelines; management; therapy; thyroid cancer; thyroid nodule; thyroid surgery; ultrasound-guided biopsy